Triboelectric Nanogenerator Prepared from Poly(vinylidene Fluoride-Hexafluoropropylene) Polymer Composite - Pattarasuda Wannarumon; Pichet Limsuwan; Pisan Sukwisute; Nuttakrit Somdock (Integrated ferroelectrics, 2023)
In this work, poly(vinylidene fluoride-hexafluoropropylene)/reduced graphene oxide films were prepared by the solution casting method with N,N-dimethylformamide (DMF) and DMF/acetone mixed solvents. The effects of reduced graphene oxide and solvent type on the morphology and crystal structure of the composite films were investigated by using scanning electron microscopy, Fourier-transform infrared spectroscopy, and Raman spectroscopy, respectively. The morphology study showed that the addition of acetone in the film process resulted in the occurrence of tiny pores on the film surfaces. The reduced graphene oxide incorporated into the PVDF-HFP was able to promote the formation of β- phase in the composites. The maximum power of 15.58 µW was obtained from the films using DMF/acetone mixture as solvent.
Keywords: Advanced Sensor and Energy Harvesting Materials; Conducting polymers and applications; Dielectric materials and actuators